(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Endoscopic septoplasty is a minimally invasive technique for correction of nasal septal deviation. It offers excellent visualization with least trauma. A retrospective study was conducted in Dept of ENT at Santosh Medical College Ghaziabad to include 50 patients who underwent endoscopic septoplasty with our novel technique. There were minimal complications with positive surgical outcomes. It helps in correction of complex deformities and deviations of septum. This makes it an ideal teaching technique.